ICE specification for piling and embedded retaining walls (Thomas Telford, 2007)
This edition is designed to be used as the new technical specification for piling & embedded walling works either on land or near to the shore. It documents the latest piling techniques & procurement methods used in the foundations sector whilst incorporating the changes introduced by the new European Standards.